2021
DOI: 10.29303/jbt.v21i3.2948
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Growth of Green Eggplant Due to Treatment of Vermicompost and NPK Fertilizer

Abstract: Green eggplant is native to the tropics. Green eggplant is one of the most popular vegetable ingredients in Indonesia. The availability of nutrients in the growing media is one of the most determining factors for the growth and yield of green eggplant. Research on vegetative growth of green eggplant due to vermicompost and NPK fertilizer treatment has been carried out from April to August 2021. This study aims to determine: (1) vegetative growth of green eggplant due to vermicompost treatment, (2) green eggpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
1
4
0
4
Order By: Relevance
“…Similar results were found for sataria grass, the application of compost increased the number of leaves = 20.63 leaves, the number of tillers = 94.97 stems, and the plant height = 45.07 cm (Kalo & Sio, 2020). Likewise Raksun et al (2021) reported that the application of vermicompost could increase the number of leaves, stem height, stem diameter and length of green eggplant leaves. The best dose of vermicompost is 18 tons for 1 hectare…”
Section: Number Of Leavessupporting
confidence: 76%
“…Similar results were found for sataria grass, the application of compost increased the number of leaves = 20.63 leaves, the number of tillers = 94.97 stems, and the plant height = 45.07 cm (Kalo & Sio, 2020). Likewise Raksun et al (2021) reported that the application of vermicompost could increase the number of leaves, stem height, stem diameter and length of green eggplant leaves. The best dose of vermicompost is 18 tons for 1 hectare…”
Section: Number Of Leavessupporting
confidence: 76%
“…Journal Of Agricultural Science And Agriculture Engineering Faculty of Agriculture, Merdeka University Surabaya,Indonesia Available on : https://agriculturalscience.unmerbaya.ac.id/index.php/agriscience/index level is very low at 2-3 tons/ha. This productivity is much lower when compared to the potential yield of long beans which can reach 20-25 tons/ha of fresh pods (Raksun et al, 2021).…”
Section: Agricultural Sciencementioning
confidence: 88%
“…Pada tanaman tomat dilaporkan bahwa kompos yang dibuat melalui fermentasi dengan bantuan cacing tanah dapat meningkatkan pertumbuhan dan hasil panen tanaman tomat. Dosis yang memberikan hasil terbaik adalah 1,8 kg kompos (Raksun, et al 2021).…”
Section: Pendahuluanunclassified